Sessile Clostridioides difficilecontribute towards recurrent C. difficileinfection. Issue 5 (27th May 2022) - Normington, Charmaine; Moura, Ines; Byrant, Jessica; Ewin, Duncan; Ford, Christopher; Wilcox, Mark; Buckley, Anthony
Abstract : C. difficile, an anaerobic spore-forming intestinal pathogen, produces up to three toxins that cause host cell damage resulting in disease, C. difficileinfection (CDI). Therapies include antibiotic treatment; however, up to 30% of cases fail primary therapy, resulting in recurrent disease, which increases patient morbidity and places a burden on worldwide healthcare systems. We have little understanding of why these therapies fail. Using a clinically validated in vitro gut model, we assess the contribution of biofilms towards recurrent disease and to investigate biofilm microbiota-C. difficile interactions. During induction of simulated CDI, C. difficile spores and vegetative cells became associated with the colonic biofilm microbiota. Vancomycin treatment did not effectively remove the biofilm C. difficile cells and recurrent infection was observed. Additionally, vancomycin therapy followed by faecal microbiota transplant did resolve the recurrent infection, but the biofilm C. difficile cells remained unaffected. In a biofilm transfer experiment, we showed that transferring biofilm encased C. difficile cells into a C. difficile naïve (but CDI susceptible model) induced CDI. Furthermore, we show that members of the biofilm community can impact C. difficile biofilm formation either acting in an antagonistic or synergistic manner. We highlight the importance of biofilms as a reservoir for C. difficile, which can be a cause for recurrent infections.